2009
DOI: 10.1136/oem.2008.041582
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic heart disease mortality study among workers with occupational exposure to ammonium perfluorooctanoate

Abstract: This exposure-response study shows no convincing evidence of increased IHD mortality risk for APFO-exposed workers at this plant. Further studies evaluating the incidence of IHD are being conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Other PFOA-exposed worker studies 30,31 also have not reported any consistent evidence of increased heart disease mortality which is likely because of the healthy worker effect. Two of these studies, 28,31 however, have incorporated internal analyses on the basis of PFOArelated job exposure matrices. Such analyses mitigate the healthy worker effect to some extent.…”
Section: Occupational Studiesmentioning
confidence: 98%
“…Other PFOA-exposed worker studies 30,31 also have not reported any consistent evidence of increased heart disease mortality which is likely because of the healthy worker effect. Two of these studies, 28,31 however, have incorporated internal analyses on the basis of PFOArelated job exposure matrices. Such analyses mitigate the healthy worker effect to some extent.…”
Section: Occupational Studiesmentioning
confidence: 98%
“…The mortality of workers ( n = 6,207) at a DuPont plant using PFOA, who were employed between 1948 and 2002, has been studied by Leonard et al (2008) and Sakr et al (2009). Serum PFOA levels among all workers at this plant in 2004 averaged 240 ng/mL, with an average of 490 ng/mL among workers in the PFOA areas (Sakr et al 2007a).…”
Section: Lipids Uric Acid Diabetes and Cardiovascular And Cerebrovmentioning
confidence: 99%
“…SMRs for ischemic heart disease (IHD) compared with U.S. and state general populations were < 1.0, as might be expected because of the healthy worker effect. Sakr et al (2009) conducted dose–response analyses of these same data using a job–exposure matrix (Kreckmann et al 2009), which used job categories and measured serum levels for 1,000 workers in 2004 to assign all cohort members to four quartiles of cumulative serum PFOA. The mean serum was 231 ng/mL.…”
Section: Lipids Uric Acid Diabetes and Cardiovascular And Cerebrovmentioning
confidence: 99%
“…As part of this robust data set, the potential association of PFOA exposure with an increased cancer mortality or incidence has been studied in both occupationally exposed (Alexander et al, 2003;Lundin et al, 2009: Alexander andLeonard et al, 2008;Sakr et al, 2007aSakr et al, , 2007bSakr et al, , 2009) and nonoccupationally exposed populations (Erikson et al, 2009), including a population in two counties of Minnesota with Drug and Chemical Toxicology, 2010;33(2): 131-137…”
Section: Introductionmentioning
confidence: 99%